Innovations and technologies for the prevention of pressure ulcers in the calcaneus - Baron, Miriam Viviane; Pavani, Ricardo Moraes; Forgiarini Junior, Luiz Alberto (Revista de Epidemiologia e Controle de Infecção, 2017)
Background and Objectives: Several prevention devices for pressure ulcers have emerged in the market recently; however, many do not meet the prevention guidelines and can contribute to increase the risk of developing ulcers. The objective of the present study was to carry out a literature review on the main innovations and technologies developed in the past ten years to prevent calcaneal pressure ulcer. Contents: The literature survey consisted of searching for papers published from January 2006 to February 2016 in Portuguese, English and Spanish. The consulted databases were SciELO, IBECS, MEDLINE, LILACS and PubMed, by combining descriptors and Boolean operators as follows: pressure ulcer AND prevention AND control OR pressure ulcer AND calcaneus OR pressure ulcer AND inventions OR pressure ulcer AND equipment AND hospital supplies OR pressure ulcer AND diffusion of innovation. The search resulted in 2,145 papers, and reading of title and abstracts allowed the selection of 14 publications that met the inclusion criteria and were included in the sample of this review. Conclusions: Innovations and technologies developed in the past ten years are useful and can be incorporated in global prevention protocols for pressure ulcers. Nevertheless, innovations and technologies for prevention of calcaneal pressure ulcers are sparse. The authors suggest the development of specific devices for prevention of calcaneal pressure ulcers based on scientific evidence. Descriptors: Pressure ulcers. Inventions. Hospital supplies and equipment. Diffusion of innovation.